2019
DOI: 10.14807/ijmp.v10i7.912
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary approach to teaching physics to students majoring in agrarian engineering and agronomy

Abstract: This study reports on interdisciplinary approach to teaching physics to the students majoring in agrarian and mechanical engineering. Physics plays a crucial role in mastering major disciplines by students of technical universities. Ukrainian higher education provides primarily mono-disciplinary approach to teaching academic and major subjects, so called teaching isolated disciplines. The interdisciplinary aspect of teaching physics corresponds to the requirements of modern society to educate competitive and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…This problem may be solved in various ways. When selecting the content of the lecture material and structuring it, we widely use the principle of generalization [10], which assumes the selection of one or several main ideas and grouping the material around this idea. The material of the physics course is grouped around the physical theories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem may be solved in various ways. When selecting the content of the lecture material and structuring it, we widely use the principle of generalization [10], which assumes the selection of one or several main ideas and grouping the material around this idea. The material of the physics course is grouped around the physical theories.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the investigations, connected with the course of lectures studied, show that the lectures allow the student to develop a positive attitude and curiosity towards science only if they have a relation to and examples of their future professional activity [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue researchers performed a number of studies on the formation of professional competence, revealed its basic principles and importance in the training of future specialists [1][2][3][4]. Researchers in their works focus on the professional training of masters in international affairs [5], border service students [6], medical physicists [7], and future agricultural production specialists [8], using an interdisciplinary approach.…”
Section: Introductionmentioning
confidence: 99%